IMAN KRISTEN DAN BUDAYA POPULAR - James A. Lola (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
Humans live in a particular cultural context; on the one side, culture is the result of human creativity, and on the other side, culture is also likely to affect humans. Currently, we are in a period of popular culture. The popular culture emphasizes pragmatic attitudes and is controlled by capitalism disguised. Christians can not be separated from the influence of popular culture. Christians are called to be able to behave in popular culture without leaving the Christian faith. This article aims to discover the relationship between the Christian faith and popular culture through a theological approach.